Project Work at All Levels - Rosalba Cárdenas (Asociación Colombiana de Profesores de Ingles, 2016)
This article focuses on project work as an alternative for language learning and teaching at all levels and in all types of educational programs. It tries to present, in an orderly manner, key aspects teachers should take into consideration to incorporate project work into their teaching, to go online with the process, student-centered, integrative and participatory trends in teaching that our present society requires.